The Development of Islamic Religious Education Android-Based Application of Salat Material for Elementary Students - Nurul Bahiyah; Wulandari Wulandari; Saluky Saluky (Al-Aulad: Journal of Islamic Primary Education, 2022)
The Covid-19 pandemic has had a significant impact on various lines of life, including the education sector. The government's policy to minimize the transmission of the virus is carried out by implementing physical distancing rules. Therefore, the government in this case the Ministry of Education and Culture (Kemendikbud) provides rules for conducting distance learning. One of the schools affected by this policy is SDI (Islamic elementary school) Losari Lor. Teaching and Learning Activities (KBM) at SDI Losari Lor, before the pandemic were completely carried out offline with a lecture model. However, during the pandemic, activities were carried out with limited face-to-face and online in accordance with the instructions of the Brebes Education Office. The weakness of KBM is that learning is less than optimal, the teacher explains the material in class in a limited way, students are required to study independently. Likewise with the subject of Islamic Religious Education (PAI). Salat material is the material taught in class II semester 2. This study aims to create an android-based learning application, in order to increase students' understanding and understanding of the material to be discussed, namely the salat material. In addition, this research is also to overcome learning that is constrained by the internet network. Data collection methods used are interview methods, direct observation methods and literature methods. While the method used in building the application is a 4D model. The steps taken are Define, Design, Develop, and Dessiminate. The software used is Microsoft Powerpoint, iSpring Suite, and Web2Apk Builder. The result of the research is an Android-based Salat application. The result of this research is a mobile learning of salat application that can be used to make teaching and learning activities more interesting and interactive. Besides the fact that the material presented to the student will be easier to understand, the application can also be accessed even without an internet network.